2011
DOI: 10.1093/ecam/nep141
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Holistic Complementary and Alternative Medicines Questionnaire (HCAMQ)—An Investigation Using Modern Psychometric Approaches

Abstract: The scientific basis of efficacy studies of complementary medicine requires the availability of validated measures. The Holistic Complementary and Alternative Medicine Questionnaire (HCAMQ) is one such measure. This article aimed to examine its construct validity, using a modern psychometric approach. The HCAMQ was completed by 221 patients (mean age 66.8, SD 8.29, 58% females) with chronic stable pain predominantly from a single joint (hip or knee) of mechanical origin, waiting for a hip (40%) or knee (60%) j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Although the scales were all adopted from previous research, the initial CFAs of two scales (out-group perception and attitude toward CAM) showed a few of the items did not load on the latent constructs at an acceptable level (ie, with loadings below .40). Based on these findings and a recently published psychometric analysis of the CAM scale (Kersten et al, 2011), we removed three items from the CAM scale and one item from the out-group perception scale. We then conducted a new CFA to test the overall fit of the measurement component of our predictive model.…”
Section: Resultsmentioning
confidence: 99%
“…Although the scales were all adopted from previous research, the initial CFAs of two scales (out-group perception and attitude toward CAM) showed a few of the items did not load on the latent constructs at an acceptable level (ie, with loadings below .40). Based on these findings and a recently published psychometric analysis of the CAM scale (Kersten et al, 2011), we removed three items from the CAM scale and one item from the out-group perception scale. We then conducted a new CFA to test the overall fit of the measurement component of our predictive model.…”
Section: Resultsmentioning
confidence: 99%
“…The five-item holistic health (HH) subscale measures beliefs about holistic health (e.g., Positive thinking can help you fight off a minor illness) on a six-point Likert scale [26]. According to the recommendation of Kersten and colleagues [33], the fourth item of the subscale was removed and the four-item version was used. Cronbach's α coefficient was 0.77 in the present study.…”
Section: Holistic Health Subscale Of the Holistic Complementary And A...mentioning
confidence: 99%
“…This questionnaire has been psychometrically validated, with good test–retest reliability 9 . However, the original proposed two-factor structure, with subscales indicating attitudes towards complementary and alternative medicine and to holistic health, has been supplanted by a revised two-factor structure using shortened subscales for these variables 10 . A low score (minimum score of 1) indicates a more positive attitude towards complementary and alternative medicine and holistic health; the maximum score of 6 indicates an extremely negative attitude.…”
Section: Methodsmentioning
confidence: 99%